Temperature-Immune High-Entropy Alloy Flexible Strain Sensor on Electrospinning Nanofibrous Membrane - Li, Wenxin; Du, Xianruo; Zhong, Yisheng; Chen, Ruixin; Wu, Yuyang; Chen, Huatan; Yan, Huangping; Liu, Yifang; Zhang, Chentao; Zheng, Gaofeng (Nano-Micro Letters, 2026)
Temperature stability is essential for the precision of flexible sensors. However, constrained by the composite principle of heterogeneous materials, the existing self-compensating methods encounter substantial challenges. To tackle this, high-entropy alloy nanofibers were utilized to construct a flexible strain sensor with inherent temperature stability. This approach leverages the electrohydrodynamic direct writing; a precursor conductive network was established through the electrospinning of a high-entropy alloy acetate and polyvinylidene difluoride solution blend. Subsequently, annealing treatment facilitated metallization, resulting in the synergistic preservation of polymer stretchability and the low temperature coefficient of resistance properties of high-entropy alloys inside the nanofibers. The test results demonstrate that the high-entropy alloys flexible strain sensor exhibits a remarkably low temperature coefficient of resistance (45.59 ppm K−1) across the range of − 10 to 70 °C, a sensitivity coefficient GF of 1.12 with a 50% strain range, and a response time of 310 ms. After 6000 stretching cycles, no baseline drift or failure occurred, indicating excellent cyclic stability. Furthermore, the outstanding temperature stability of the sensor was validated through wearable application and robotic hands strain sensing conducted under varied environment temperatures. This work provides a viable design pathway for developing flexible sensors with an inherently low temperature coefficient of resistance. Highlights: 1 High-entropy alloy fiber was fabricated via electrohydrodynamic direct writing and subsequently metallized at the nanoscale to form uniform high-entropy alloy lattices within polymer nanofibers. 2 The metallized temperature-immune strain sensor exhibits low temperature coefficient of resistance (45.59 ppm K-1) and excellent cyclic stability (6000 cycles), enabling reliable strain measurements across a wide temperature range. 3 Wearable human joint monitoring and robotic grasping tests demonstrate the sensor’s high reliability and accurate response under complex thermal environments.